Understanding Freedom (Existential Analysis: Journal of the Society for Existential Analysis, 2000)
Since freedom seems to be a foundation of human existence my priority is to take a closer look at the concept of freedom in order to unravel its mystery and perhaps to move away from the prevailing, but often confusing idea of what it means to be free. It is also my intention to provide illustrations from my clinical practice of how men sabotage their opportunities of becoming 'free spirits' and renounce a dignified existence by resorting to behaviours that clearly oppose or masquerade as freedom. My hope is that out of these considerations emerges a sketch of the individual who has a clearer idea of how to increase and use his capacity to make free choices.